1998
DOI: 10.1542/peds.101.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Immune System by Human Milk and Infant Formula Containing Nucleotides

Abstract: Infant formula fortified with nucleotides enhanced H influenzae type b and diphtheria humoral antibody responses. Feeding human milk enhanced antibody responses to OPV. Dietary factors play a role in the antibody response of infants to immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
146
2
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(168 citation statements)
references
References 47 publications
16
146
2
4
Order By: Relevance
“…These results suggested that nucleotides could act as prebiotics favouring the proliferation of the beneficial flora and inhibiting that of potential pathogens. These results support clinical findings showing a low incidence of acute diarrhoea in infants fed nucleotide supplemented formula in developing (Brunser et al, 1994) and developed countries (Pickering et al, 1998).…”
Section: Dietary Nucleotides and Defence Against Infectionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results suggested that nucleotides could act as prebiotics favouring the proliferation of the beneficial flora and inhibiting that of potential pathogens. These results support clinical findings showing a low incidence of acute diarrhoea in infants fed nucleotide supplemented formula in developing (Brunser et al, 1994) and developed countries (Pickering et al, 1998).…”
Section: Dietary Nucleotides and Defence Against Infectionsupporting
confidence: 89%
“…Refeeding after malnutrition did not produce any significant changes either in serum total and specific immunoglobulins against a-casein and b-lactoglobulin or in saliva IgA levels (Martínez-Augustín et al, 1997). Finally, a recent study has also shown that dietary nucleotides may modulate the immune response in normal infants, enhancing the production of specific IgG against low response antigens, namely H. influenzae type b, a bacterium responsible for meningitis episodes in early infancy (Pickering et al, 1998).…”
Section: Modulation Of Immunoglobulin Production By Nucleotidesmentioning
confidence: 99%
“…The results from these studies are controversial. However, a well-executed randomized trial was recently reported, showing that breastfed infants exhibit enhanced specific antibody titre to some, but not all, vaccines (Pickering et al 1998). Very little work has been carried out on the cell-mediated immune response in breast-fed v. bottle-fed infants.…”
Section: Maternal Milk and Immune Modulationmentioning
confidence: 99%
“…The primary justification for these additions was evidence in animals and humans that dietary NT enhance development of the gastrointestinal and immune systems. 1,2 A lower incidence of diarrhea, 3-5 enhanced response to vaccination, 4,6,22 and effects on natural killer cell activity 7 and immune cell subset distribution 8 have been reported in term infants. We are aware of only one published study reporting dietary NT effects in preterm infants: serum concentrations of immunoglobulin G to b-lactoglobulin were significantly greater in preterm infants fed NT-supplemented formula for 30 days.…”
mentioning
confidence: 99%
“…Three randomized, well-controlled, multi-center studies in term infants enrolled a total of more than 300 infants into each of the control and study groups. 4,6,21 Two of the studies reported that dietary NT supplementation enhanced infants' responses to vaccination, 4,6 while one reported that immune cell profiles of infants fed NT-supplemented formula tended to be more like those fed human milk. 8 A more recent study reported that infants fed NTsupplemented formula had significantly higher responses to tetanus toxoid.…”
mentioning
confidence: 99%